2018
DOI: 10.1159/000499378
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds are Associated with Postural Instability and Gait Disturbance Subtype in People with Parkinson’s Disease

Abstract: Objectives: The motor symptoms of Parkinson’s disease (PD) vary among patients and have been categorized into 3 subtypes: tremor dominant, akinetic rigidity, and postural instability and gait disturbance (PIGD). Cerebral microbleed (CMB) is prevalent in people with PD and is associated with some nonmotor symptoms. The present study investigated the association between CMB and the motor subtypes of PD. Materials and Methods: From 2009 to 2017, medical records and brain magnetic resonance imaging (MRI) reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A recent study using ASL showed TD to have more hypoperfusion in the temporo–parieto–frontal network while PIGD showed hypoperfusion in a predominantly posterior pattern as well as hyperperfusion in the BG, although these differences were removed when levodopa medication, and disease severity and duration were controlled for 27 . Comparatively, in a recent structural study PIGD were associated with an increased prevalence of thalamic and WM cerebral microbleeds (ie, small chronic brain hemorrhages caused by abnormalities of small brain vessels) when compared to TD and AR 92 . These results suggest that CBF and other cerebral blood parameters could be valuable imaging techniques to differentiate between PD subtypes.…”
Section: Resultsmentioning
confidence: 96%
“…A recent study using ASL showed TD to have more hypoperfusion in the temporo–parieto–frontal network while PIGD showed hypoperfusion in a predominantly posterior pattern as well as hyperperfusion in the BG, although these differences were removed when levodopa medication, and disease severity and duration were controlled for 27 . Comparatively, in a recent structural study PIGD were associated with an increased prevalence of thalamic and WM cerebral microbleeds (ie, small chronic brain hemorrhages caused by abnormalities of small brain vessels) when compared to TD and AR 92 . These results suggest that CBF and other cerebral blood parameters could be valuable imaging techniques to differentiate between PD subtypes.…”
Section: Resultsmentioning
confidence: 96%
“…Distinct from other subtypes, PIGD is characterized by rapid progression, comorbidity with cognitive dysfunction, and motor symptoms that are unresponsive to levodopa treatment [20]. Several brain conditions are associated with PIGD, including gray matter atrophy [34], basal ganglia dysfunction [35], white matter lesions [36], and cerebral microbleeds [37], indicating a multifaceted brain pathology. Motor learning is crucial for the control of postural stability and gait.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exploration between movement disorder and CMB still rare and the conclusion was controversial. Only two studies have found the number of CMBs is related to gait disturbances [10,11] and most other studies did not nd positive results between CMBs and motor performance [3,12,13], which implied the relationship between gait and CMB was still unclear and need further exploration.…”
Section: Introductionmentioning
confidence: 99%